PENGARUH PENGGUNAAN BUKU SAKU DIGITAL BERBASIS ANDROID TERHADAP PENGETAHUAN TENTANG BAHAN DAN ALAT PRAKTIK LABORATORIUM - Lia, Lismiati; Hernita, Maini; Silvanora, Rice (NHM PRESS, 2023)
A laboratory is a place used to carry out testing activities. Before starting to carry out practical activities in the laboratory, as a practitioner you must be familiar with the practical tools and all the functions of basic equipment commonly used in the laboratory. Practical tools can usually be damaged or even dangerous if they do not comply with usage procedures. So practical participants need to have knowledge about tools and materials through easy-to-understand media, one of which is an Android-based digital pocket book. This research aims to determine the effectiveness of demonstrations and digital pocketbooks on knowledge about laboratory practical tools and materials. Using a quasi-experimental research method, with a two group pre test post test design. The statistical analysis test used the Paired sample T test and the Wilcoxon Signed Ranks Test. The results of this research showed that as many as 25% of respondents had poor knowledge before being given the demonstration. As many as 8% of respondents had poor knowledge before being given the digital pocket book. After being given the intervention, respondents' knowledge increased to 100% in the demonstration group and 100% in the digital pocket book media. The results of data analysis showed that p value = 0.181 or p > 0.05, there was no difference between demonstrations and digital pocket books on knowledge about laboratory practical tools and materials. The use of digital pocket book media is no more effective than demonstrations in introducing laboratory practical tools and materials.